Vaksinasi Covid-19 dalam Perspektif Maqashid al-Syari’ah: Sebagai Hak atau Kewajiban - Ridwan, Muannif (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2023)
This study discusses Covid-19 Vaccination from the Perspective of Maqashid Syariah with the aim of showing where the position of vaccination for the community is based on the principle of benefit, as this is one of the substances of maqashid syariah. The main problem of this research is whether Covid-19 vaccination is a right or obligation for every community and how this vaccination is given from the perspective of maqashid sharia. This research uses a qualitative descriptive method or also known as library research. This research resulted in a conclusion, namely at the beginning of carrying out the Covid-19 vaccination is a right for the community and based on this right, it is only carried out for those who want and need it, however, gradually the spread of the corona virus has increased, causing many people to die and be exposed, so the government, in this case, requires people to vaccinate so that people have good immune system. Apart from that, Indonesia has also become an emergency zone where all people are required to vaccinate, and if viewed from the maqasid sharia viewpoint, it is mandatory from a sharia viewpoint, the implementation of the Covid-19 vaccination is to reduce the spread and expansion of the corona virus outbreak and for the benefit of society and protect the lives and souls of fellow human beings by inhibiting and reducing the death rate from the virus.